Legal Analysis of the Effective Use of School Operational Assistance Funds in North Halmahera District - Rina Wahyuni; Husen Alting; Suwarti Suwarti (Syntax Corporation Indonesia, 2023)
Regulation of the Minister of Education and Culture Number 6 of 2021 Concerning the Technical Guidelines for Regular School Operational Assistance states that the purpose of providing BOS Funds is to help with school operational costs, increase flexibility and quality of learning for students. The government hopes that every poor citizen can get an education and experience a better teaching and learning process. school operations in North Halmahera Regency. This study uses qualitative research. The population study was all schools in West Kao District, North Halmahera Regency with a sample of 11 schools. This research was conducted from June to August 2022. The research instruments were interviews and observations. The results showed that the use of BOS funds had not been effective so that the quality of education was still relatively low.